Studi Keanekaragaman Flora dan Kajian Potensi Pekarangan sebagai Tapak Pelestarian Cendana di Desa Teun, Belu dan Lokomea Timor Tengah Utara - NTT - Albert Husein Wawo; Ninik Setyowati (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2011)
The study of plant diversity and investigation of home garden potential as conservation site for sandalwood at Teun and Lokomea villages had been carried out at East Nusa Tenggara Province. The result showed that home garden in Teun village have 24 species of plant and in Lokomea village have 31 species of plant. Diversity index in both locations are 1.163 and 1.151 with similarity index is 0.80. Based on purpose of flora at home gardens in both villages are divided in to 3 groups are fruit, commercial (estate crops) and vegetable crops. Majority of the local people in both villages have planted mango, coconut, banana, tamarind and sandalwood at their home gardens.  Result of investigation of home garden potency showed that home garden in both villages have 3 points of strength are ecological, economical and social culture potency so that home garden in both villages can be developed as conservation site for sandalwood.